Perspektif Hukum Islam dalam Praktik Kirim Sesajen Pernikahan di Petilasan Taman Sokosewu Sukorejo Ponorogo - Jud, Hilmillathif Dzil; Ayu, Diyan Putri; SJ, Ahmad Syafi'i (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Indonesia is a country with diverse religions, where Islam, as the majority religion, provides comprehensive guidelines governing the relationships between humans and God, among individuals, and with the environment. In Islam, marriage is regulated in detail to ensure a relationship that is blessed and adheres to religious principles. In Java, the acculturation between Islamic marriage and Javanese customs has created a unique marriage tradition that integrates Islamic values with local wisdom. An example of this acculturation is the practice of sesajen in wedding ceremonies in Sukorejo, Ponorogo. This practice is a cultural heritage containing spiritual elements, influenced by Hindu traditions that have blended with Islam. This research aims to understand the origins of the cultural acculturation between Islamic marriage and Javanese customs and to assess the legal perspective on the practice of sesajen according to Islamic law in Sukorejo. The main focus is to examine how sesajen is accepted or conflicts with Islamic principles, and how this tradition adapts to the local context while preserving cultural and religious values.